Incorpórese al código de la niñez y adolescencia, garantías al pago de las pensiones alimenticias, por un aval subsidiario - Abarca León, Tarcila Deida (2014)
Children and adolescents are an important sector of the Ecuadorian population, the Ecuadorian Constitution enshrines the rights for this group of people, such as priority groups, for it is the State that has the duty to protect, support and promote the integral development of children and adolescents, the process of growth, maturation and deployment of their intellect and their abilities, potential and aspirations, in the family, school, social and community environment of affection and security. This environment will allow satisfaction, affective-emotional and cultural, social needs with the support of national and local intersectoral policies, and provide protection for a dignified life, socio-economic conditions that allow their full development, a nutritious, balanced and sufficient food ; recreation and games, quality education, clothing and housing with all basic amenities. As can be seen that children and adolescents will always respect the interests of the child, considering the need to maintain a fair balance between the rights and duties of children and adolescents in the manner that best suits the realization of their rights and interests, so that where there is doubt about the age of a person is presumed to be a child, teenager girl before; the person who has not attained the age of eighteen. The Convention has a set of universal rules to which all countries can join. Children are not considered property of their fathers or helpless recipients of charity. They are considered human beings and their rights holders. According to the perspective presented by the Convention, children are individuals and members of a family and community, with rights and responsibilities appropriate for their age. Recognize the rights of children in this way allows them to focus on as whole beings. If at one time the needs of children were considered marketable, they have now become fundamental rights. The children were no longer passive recipients of benefits to become autonomous beings and subjects with rights, especially the right to education until the completion of their studies and achieve their professionalism, their personal and professional development.